Prevalence of lower respiratory tract infection in tertiary care hospital, Thane - Joshi, Shrikant; Shaikh, Kamil; Kulkarni, Vrushali V. (International Journal of Contemporary Pediatrics, 2021)
Background: World health organization (WHO) predicted lower respiratory tract infections (LRTI) as primary cause of mortality world-wide. The present study was undertaken to know the various types of LRTI in children <5 years of age and analyze factors influencing the morbidity and mortality of those cases. Methods: Prospective cross-sectional study for 100 infected children with LRTI was conducted in a tertiary care hospital of metropolitan city. Demographic, clinical history and examination, necessary investigations were performed and followed regularly for desired outcome. Results: 51% children were in the age-group of 1 to 5 years who reported acute lower respiratory tract infection (ALRTI) and 49% were below 1 year age. The study reported LTRI incidence in 63% male and 37% female children whereas the family history of incidence of LRTI was present in 18% cases. Fever, cough and retraction complaints were the prominent symptoms. Hyperinflation was the major finding in chest X-ray. Streptococcus pneumoniae was the common bacterial pathogens isolated. Bronchiolitis was the commonest cause (39%) followed by lobar pneumonia (37%). Conclusions: Various types of clinical presentations, risk factors and types of LRTI in children less than 5 years of age were studied. A result of this study will be useful to understand the etiology and bacterial pathogens in management of clinical outcome. Modifiable risk factors for LRTI like family history, past history, immunization status, and malnutrition can be tackled through effective health education of the community, leading to a healthy society.